2018
DOI: 10.1021/acs.orglett.8b00684
|View full text |Cite
|
Sign up to set email alerts
|

Angular-Shaped Naphthalene Bis(1,5-diamide-2,6-diylidene)malononitrile for High-Performance, Air-Stable N-Type Organic Field-Effect Transistors

Abstract: The synthesis, characterization, and application of two angular-shaped naphthalene bis(1,5-diamide-2,6-diylidene)malononitriles (NBAMs) as high-performance air-stable n-type organic field effect transistor (OFET) materials are reported. NBAM derivatives exhibit deep lowest-unoccupied molecular orbital (LUMO) levels, suitable for air-stable n-type OFETs. The OFET device based on NBAM-EH fabricated by vapor deposition exhibits a maximum electron mobility of 0.63 cm V s in air with an on/off current ratio ( I/ I)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Several attempts have been made to enhance the stability and charge-transporting properties of the active semiconducting layer. Good results have been reported with polymer-based devices, but recently, small molecules are being explored as a competitive alternative to the conjugated polymer owing to their diverse merits of easier synthesis, functionalization, high purity, well-defined structure, and monodisperse molecular weight, which enable large-scale vapor and solution-based fabrication. Ambipolar small molecules are in high demand because they provide great potential to meet the application requirements such as high functionality, low power consumption, and robustness …”
Section: Introductionmentioning
confidence: 99%
“…Several attempts have been made to enhance the stability and charge-transporting properties of the active semiconducting layer. Good results have been reported with polymer-based devices, but recently, small molecules are being explored as a competitive alternative to the conjugated polymer owing to their diverse merits of easier synthesis, functionalization, high purity, well-defined structure, and monodisperse molecular weight, which enable large-scale vapor and solution-based fabrication. Ambipolar small molecules are in high demand because they provide great potential to meet the application requirements such as high functionality, low power consumption, and robustness …”
Section: Introductionmentioning
confidence: 99%
“…Many of n-type OSCs are still unstable when operated in air; this is ascribed to the lowest unoccupied molecular orbital (LUMO) levels which are not sufficiently low . Therefore, enormous efforts have been dedicated to develop air-stable n-type OSCs. , Among n-type OSCs, diketopyrrolopyrrole, , naphthalene diimide, benzothiadiazole, , and isoindigo are representative units used not only in acceptor parts of donor–acceptor polymers but also in small-molecule semiconductors. Like these units, introduction of strong electron-withdrawing groups, such as carbonyl groups, , diimide groups, thiadiazole groups, , and cyano groups, is an effective approach for designing novel n-type OSCs.…”
Section: Introductionmentioning
confidence: 99%
“…Bisisatin (Scheme ) is a synthetic precursor of bisisoindigo and also a promising n-type organic material due to the planar framework with four electron-withdrawing carbonyl groups. Moreover, when the β-position carbonyl group is modified by a dicyanomethylene group, we can further lower the LUMO levels to obtain potentially air-stable n-type materials. To date, two types of bisisatin derivatives have been reported: one has a fused ring system with naphthalene core (Scheme a), and another is bridged by a central single bond (Scheme b) . However, the latter takes a nonplanar structure twisted around the central single bond when the β-carbonyl groups are replaced with dicyanomethylene groups similarly to Scheme d, and this nonplanar framework is not preferable for OFET devices.…”
Section: Introductionmentioning
confidence: 99%
“…Air-stable n ‑type OFET materials must generally have high electron affinity (EA), preventing common redox reactions of water and oxygen that can occur during device operation, causing degradation. Incorporating strong electron-withdrawing substituents such as dicarboxylic imides onto rylenes and cyanos onto quinoidal oligothiophenes and diketopyrrolopyrrole derivatives has been proved to be an effective strategy for lowering LUMO energy levels and strengthening intermolecular π–π interaction, supporting the realization of air-stable n -type OFETs.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that n ‑type OFETs that are based on this core have promising electron mobilities under ambient conditions . Recently, dicyanomethylene-substituted compounds have attracted much interest as n ‑type OSCs because of the superior electron-withdrawing characteristics of their cyanovinyl groups, which stabilize their LUMO levels . Certain dicyanomethylene-substituted quinoidal OSCs have shown very promising performance in OFET devices.…”
Section: Introductionmentioning
confidence: 99%